Pengaruh Beban Pajak, Mekanisme Bonus, Exchange Rate, dan Tunneling Incentive terhadap Indikasi melakukan Transfer Pricing - Ayulianti, Salsabila; Mahpudin, Endang (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to see the influence of Tax Burden, Bonus Mechanism, Exchange Rate, and Tunneling Incentive on Indications for Transfer Pricing by conducting tests on companies as consideration for making policies. The analytical method used is the multiple linear regression analysis method with the help of the SPSS 25 application. This research shows that the results show that the Tax Burden, Bonus Mechanism and Exchange Rate partially have no effect on the indication of transferring pricing, while the Tunneling Incentive variable partially influences the indication of transferring pricing. Tax burden, Bonus Mechanism, Exchange Rate and Tunneling Incentive simultaneously positive influence indications for Transfer Pricing in Manufacturing Companies in the Textile and Clothing Industry Sector listed on the IDX for the 2017-2023 period.